International Conference on Health, Safety and Environment in Oil and Gas Exploration and Production 2012
DOI: 10.2118/156848-ms
|View full text |Cite
|
Sign up to set email alerts
|

Noise Reduction Interventions in the Norwegian Petroleum Industry

Abstract: Noise exposure is still an important challenge to a safe and healthy work environment, both offshore and onshore. Studies over the last 10 years show that the noise exposure (expressed as the "average noise indicator") remains mainly unchanged with no significant reduction in the past decennium. Furthermore, several reports indicate that workers in the petroleum industry are exposed to high noise levels and the risk of developing noise-related hearing loss can't be neglected. Noise induced hearing loss is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2002, Zacchariasen and Knusden stated that there is a problem with high noise exposure in the Norwegian offshore industry (Zachariassen and Knudsen 2002 ). Nistov et al ( 2012 ) in a later study reported that there is a high noise exposure level, a risk of NIHL and a need for preventive measures in this industry.…”
Section: Resultsmentioning
confidence: 99%
“…In 2002, Zacchariasen and Knusden stated that there is a problem with high noise exposure in the Norwegian offshore industry (Zachariassen and Knudsen 2002 ). Nistov et al ( 2012 ) in a later study reported that there is a high noise exposure level, a risk of NIHL and a need for preventive measures in this industry.…”
Section: Resultsmentioning
confidence: 99%
“…In 2002, Zachariasen et al [8] stated that there is a problem with high noise exposure in the Norwegian Offshore. Nistov et al [9] in a later study reported that there is a high noise exposure level a risk of NIHL and a need for preventive measures in this industry. Ross et al [10] however found that offshore workers exept for divers had a normal hearing and so did Johnson and Gann in a former study [11].…”
Section: Mini Reviewmentioning
confidence: 99%